The eLearning designer's handbook : a practical guide to the eLearning development process for new eLearning designers - Slade, Tim, ....- ([s.l.] : Tim Slade, 2020)
LEARN HOW TO DESIGN ELEARNING THAT DELIVERS RESULTS (AND DOESN'T SUCK)! When you're tasked with creating your very first eLearning course, it can be hard (and downright scary) trying to figure out where to begin. You likely have a million questions running through your head. How do you plan your project and set it up for success? How do you collect learning content from your subject matter experts? Why do you need an eLearning storyboard, and how do you write one? How do you develop a prototype of your eLearning course? And, what the heck is a prototype anyway? When and where should you include interactivity? When should you let your SMEs review your course? And what's a “SME” again? And what do you do when they don't give you feedback? Trying to get answers to all of these questions can quickly leave you saying to yourself, “I don't think I'm cut out for this eLearning thing!” But, here's some good news: you're not alone! The truth is, most eLearning designers entered fell, stumbled, and dropped into the world of eLearning entirely by accident. This is where the second edition of The eLearning Designer's Handbook can help! In this book, Tim Slade will show you that the eLearning development process doesn't have to be as complicated as it might seem. If you're new to eLearning, Tim will walk you through the complete eLearning design and development process, providing you practical tips and advice, based on his own experience working as an eLearning designer for over a decade.
With the second edition of The eLearning Designer's Handbook, you'll discover how to... Plan your eLearning project by conducting a kickoff meeting with your stakeholders. Conduct a needs analysis and recommend a training solution. Draft an eLearning project plan and development timeline. Define the learning objectives and create a blended training solution. Collect and organize your learning content into a design document. Create a course outline and draft a storyboard of your eLearning course. Create a prototype and develop your course with an eLearning authoring tool. Incorporate interactivity into your eLearning course. Reduce cognitive load and increase learning retention. Deliver and measure the effectiveness of your eLearning course. Conduct a retrospective at the end of your project.